The Extent of Institutional Compatibility in Ministries in Jordan - Alkhawaldeh, Khleef A. (Dirasat: Human and Social Sciences, 2023)
Objectives: This study examined the extent to which organizational structures, personnel, and budgets are compatible with the core functions and strategic objectives of ministries in Jordan. Methods: Details of organizational structures are taken from administrative organization bylaws and ministries’ websites. Data of employees and budgets for the years 2018-2020 published in Law No. (5) for the Year 2021, General Budget Law for the Fiscal Year 2021, and in Law No.(4) for the Year 2020, General Budget Law for the Fiscal Year 2020. The study calculated the ratio of core functions units to the total number of organizational units. It also calculated the ratio of employees working in core functions units to the total number of employees. In addition, it calculated the ratio of the budgets for core functions to the total budgets excluding subsidies for public institutions and support for general government units (allocations for other institutions and corporations). Results: The results of the study indicate that the average percentage of core functions units in the organizational structure = 61%. The results also indicate that the average ratio of the budgets of the core functions units to the total budget = 69%, while the average ratio of employees of core function units to the total number of employees = 40%. This reveals the focus on core functions in the budget and organizational structure dimensions at a satisfactory level other than the human resource dimension. The results of the correlation test indicate that there is no statistically significant correlation between the weight of the core functions in the structure, staff and budget on the one hand, and their weight in the strategic objectives on the other hand. The outputs of one-sample t-test indicate that the average ministries’ excellence assessment scores are not significantly different from the lower third of the assessment scale. Conclusions: This means that there is no alignment between the strategic objectives of the ministries and their structures, staff and budgets. Low excellence scores for ministries indicate a mismatch between core functions and institutional capabilities.